Doing qualitative research for beginners: basic underlying steps and related issues - Sheikh Ahmad, Ismail; Bsharat, Tahani; Nordin, Mohd Shukri; Nik Abdullah, Nik Md. Saiful Azizi; Shamsuddin, Aizat; Salleh, Norsaremah (An-Najah National University, 2025)
Aim: This article guides novice researchers in preparing a basic qualitative research proposal. It covers the underlying reasons for conducting qualitative research, key concepts, and the basic process flow in preparing a doable qualitative proposal: research problem, central research question, research questions, and corresponding interview questions. Methodology: Several key steps in preparing the proposal are explained and supported with tables or illustrations. Qualitative research was selected because, as Creswell and Poth (2018) and Tracy (2020) noted, it effectively examines complex social phenomena. Qualitative approaches capture the complexity and diversity of human experiences, especially when discussing complex motivations, beliefs, and processes that are difficult to measure. Findings: The paper focuses on important methodological considerations like research problem formulation, research questions, and interview question design, giving new researchers a basic understanding of how Creswell and Poth (2018) and Tracy (2020) noted to create a rigorous qualitative proposal. Conclusions: Rather than presenting an empirical study, this paper serves as a methodological guide, offering a structured framework for conducting qualitative research and ensuring methodological rigor in generating meaningful insights. Recommendations: It aims to equip early-stage researchers with the necessary skills to navigate qualitative inquiry effectively through interview-based approaches.